A covalent organic framework material for removing mercury ions from water, and its preparation method and application

By synthesizing covalent organic framework materials in a standing reaction at room temperature, it solves the harsh and time-consuming problems of traditional COFs synthesis methods and achieves efficient adsorption and removal of mercury ions in water, which has good application potential and industrial value.

CN118165203BActive Publication Date: 2025-01-21HENAN BUSINESS SCI RES INST +2
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410352128.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-04-10
Publication Date
2025-01-21
Estimated Expiration
2044-04-10

AI Technical Summary

Technical Problem

Existing sewage treatment plants are difficult to effectively remove heavy metal mercury ions from urban sewage, resulting in frequent detection in the environment. The synthesis method of traditional covalent organic frame materials (COFs) is harsh, time-consuming, complex preparation procedures and high cost. , limiting its promotion and application in sewage treatment.

Method used

Using a static reaction method at room temperature, p-phenylenediamine and trialdehyde-phloroglucinol are polycondensed in a mixed solvent, and then a scandium trifluoromethanesulfonate catalyst is added to quickly synthesize a stable covalent organic framework material. This method simplifies the preparation process, shortens the time, and reduces the cost.

Benefits of technology

It achieves efficient adsorption and removal of mercury ions in water, with fast adsorption rate and good selective adsorption performance. It is suitable for commercial promotion and is suitable for the synthesis of a variety of COFs materials with different structures.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_3
    Figure SMS_3
  • Figure SMS_5
    Figure SMS_5
Patent Text Reader

Abstract

The present invention belongs to the technical field of environmentally friendly new materials, and discloses a covalent organic framework material for removing mercury ions in water, a preparation method thereof, and an application thereof. The preparation method comprises the following steps: using p-phenylenediamine and trialdehyde phloroglucinol as monomers, and preparing the covalent organic framework material by Schiff base reaction at room temperature. The COFs prepared by the present invention using a mild and rapid room temperature synthesis method exhibits a good adsorption effect on mercury ions in water, and has a selective recognition ability. The material preparation operation is simple, and large-scale synthesis at the gram level can be achieved, and it has good application prospects in the adsorption and separation of highly toxic mercury ions in water environments.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of environmentally friendly new materials, and specifically relates to a covalent organic framework material for removing mercury ions in water, and a preparation method and application thereof. Background Art

[0002] Heavy metal mercury is extremely toxic and is considered one of the most harmful heavy metal pollutants. Mercury ions are difficult to degrade in the natural environment and are highly soluble. Mercury in the environment can enter aquatic organisms and the human body through the enrichment of the food chain and become high-concentration mercury ions, which seriously endanger human health and ecological safety. Studies have shown that existing sewage treatment plants cannot effectively remove heavy metal mercury ions in urban sewage, resulting in its frequent detection in a variety of environmental media such as rivers, surface water, sediments, and soil. Although the exposure level of heavy metal ions is low, its pollution is actually on the rise. Therefore, it is urgent to study new methods to effectively remove heavy metal mercury ions in water.

[0003] Adsorption is an important method for removing heavy metal mercury ions, and the design and key preparation technology of high-performance adsorbents are the core elements in the field of adsorption. Covalent organic framework materials (COFs) are organic porous materials with a periodic network structure formed by light elements connected by covalent bonds. They not only have the advantages of high specific surface area, regular and orderly pores and easy functional modification, but also have good thermal stability and chemical stability. They have good application prospects in the field of heavy metal adsorption and separation. At present, most of the research on mercury ion adsorption materials focuses on the modification of groups such as thiol and methylthiol on the surface of the material, such as modifying specific groups after the synthesis of COFs or pre-setting the organic monomers modified with the above specific groups and then synthesizing functionalized COFs. The strong chelation between mercury ions and thiol groups makes COFs show excellent adsorption performance for mercury ions. However, most traditional COFs materials are synthesized by solvent thermal method, which requires about 3 days of reaction at high temperature. The reaction conditions are relatively harsh and time-consuming. On this basis, whether it is pre-modification with organic monomers or post-modification of COFs synthesis to introduce thiol groups, it will increase the complexity and time cost of the preparation process, which is not conducive to its promotion and application in actual sewage treatment. Therefore, developing a simple, fast, and low-cost COFs material synthesis strategy that can be used for efficient adsorption and removal of mercury ions in water is a key technical problem that needs to be solved urgently. Summary of the invention

[0004] In view of the problems and shortcomings in the prior art, the object of the present invention is to provide a covalent organic framework material for removing mercury ions in water, and a preparation method and application thereof.

[0005] Based on the above purpose, the present invention adopts the following technical solution:

[0006] The first aspect of the present invention provides a method for preparing a covalent organic framework material for removing mercury ions in water, comprising the following steps:

[0007] (1) dissolving p-phenylenediamine and trialdehyde phloroglucinol in a mixed solvent, and allowing to react at room temperature to obtain a mixed solution;

[0008] (2) adding scandium trifluoromethanesulfonate to the mixed solution obtained in step (1), and allowing the mixture to react at room temperature. After the reaction is completed, separating the insoluble matter from the reaction solution, washing the insoluble matter, and drying the insoluble matter to obtain the covalent organic framework material for removing mercury ions in water.

[0009] Preferably, the molar ratio of p-phenylenediamine to trialdehyde phloroglucinol in step (1) is 3:2.

[0010] Preferably, the mixed solvent in step (1) is a mixed solvent of 1,4-dioxane and 1,3,5-trimethylbenzene.

[0011] Preferably, the volume ratio of 1,4-dioxane to 1,3,5-trimethylbenzene in the mixed solvent is (1-5):1.

[0012] More preferably, the volume ratio of 1,4-dioxane to 1,3,5-trimethylbenzene in the mixed solvent is 4:1.

[0013] Preferably, the molar ratio of p-phenylenediamine to scandium trifluoromethanesulfonate in step (2) is (25-100):1.

[0014] More preferably, the molar ratio of p-phenylenediamine to scandium trifluoromethanesulfonate is 25:1.

[0015] Preferably, the standing reaction time in step (1) and step (2) is 10 to 60 min.

[0016] Preferably, the detergent used to wash the insoluble matter in step (3) is at least one of methanol, ethanol and acetone.

[0017] Preferably, in step (3) and step (4), the drying temperature is 50 to 100° C. and the drying time is 10 to 24 h.

[0018] The second aspect of the present invention provides a covalent organic framework material for removing mercury ions in water, which is prepared by the method of the first aspect.

[0019] The third aspect of the present invention provides the use of the covalent organic framework material as described in the second aspect in water purification.

[0020] Preferably, the covalent organic framework material is used to adsorb and remove mercury ions in water. More preferably, when the covalent organic framework material is used as a water adsorbent, 0.05 g to 10 g of the covalent organic framework material can be added per liter of water with a mercury ion concentration of 0.05 mg / L to 20 mg / L.

[0021] Compared with the prior art, the present invention has the following beneficial effects:

[0022] (1) Compared with the traditional high-temperature and high-pressure hydrothermal synthesis of COFs materials, the present invention adopts a room temperature synthesis method to rapidly polycondense p-phenylenediamine and trialdehyde phloroglucinol under the action of scandium trifluoromethanesulfonate catalyst to obtain a stable covalent organic framework material. The preparation method of the present invention is simple to operate and has a short preparation time (<1 h). This mild and rapid preparation method can achieve large-scale synthesis at the gram level and can also be extended to the synthesis of COFs materials with various structures.

[0023] (2) The COFs material prepared by the technical solution provided by the present invention has the advantages of fast adsorption rate and good selective adsorption performance for mercury ions. In the embodiment of the present invention, the COFs material has a high adsorption rate and good selective adsorption performance for 0.1 mg / L Hg 2+ The adsorption removal rate can reach 81% to 91%, and the coexistence of other metal ions in the mixed pollutant system does not significantly affect the adsorption effect of mercury ions. The research on the application of the COFs material prepared by the room temperature synthesis method proposed in the present invention in the removal of mercury ions in water has not been reported, and it has good application potential and is suitable for commercial promotion. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 This is the X-ray diffraction (XRD) diagram of the COF-1 material in Example 1 of the present invention.

[0025] Figure 2 This is a scanning electron microscope (SEM) image of the COF-1 material in Example 1 of the present invention.

[0026] Figure 3 This is a graph showing the adsorption data of heavy metal mercury ions by the COFs materials in Examples 1 to 4 of the present invention.

[0027] Figure 4 It is a fitting data diagram of the thermodynamic adsorption curve of heavy metal mercury ions by the COF-1 material in Example 1 of the present invention and the Freundlich isothermal adsorption model; wherein a is the thermodynamic adsorption curve of the COF-1 material for heavy metal mercury ions; b is a fitting data diagram of the Freundlich isothermal adsorption model for the adsorption of mercury ions on the COF-1 material.

[0028] Figure 5It is a kinetic adsorption curve of heavy metal mercury ions by the COF-1 material in Example 1 of the present invention and a fitting data diagram of the pseudo-second-order kinetic model; wherein a is the kinetic adsorption curve of heavy metal mercury ions by the COF-1 material; b is a fitting data diagram of the pseudo-second-order kinetic model for the adsorption of mercury ions on the COF-1 material.

[0029] Figure 6 This is a diagram showing the selective adsorption and removal effect of heavy metal mercury ions by the COF-1 material in Example 1 of the present invention. DETAILED DESCRIPTION

[0030] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below through embodiments in combination with the accompanying drawings. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0031] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present application will be described in detail below with reference to the accompanying drawings and in combination with the embodiments.

[0032] 1. Preparation of covalent organic framework materials for removing mercury ions from water

[0033] Example 1

[0034] A method for preparing a covalent organic framework material for removing mercury ions from water comprises the following steps:

[0035] (1) Weigh 126.2 mg of trialdehyde phloroglucinol and 97.3 mg of p-phenylenediamine into a 50 mL conical flask, add 19.2 mL of 1,4-dioxane and 4.8 mL of 1,3,5-trimethylbenzene, dissolve them by ultrasonication, and allow to react at room temperature for 30 min to obtain solution A;

[0036] (2) Add 18 mg of scandium trifluoromethanesulfonate to solution A, dissolve it by ultrasonication, and allow to react at room temperature for 30 min to obtain solution B;

[0037] (3) Solution B was centrifuged to obtain insoluble matter, which was washed three times by centrifugation with methanol and vacuum dried at 80°C for 12 h. The obtained COF material was called COF-1 material.

[0038] Example 2

[0039] A method for preparing a covalent organic framework material for removing mercury ions from water. The preparation method is basically the same as that of Example 1, except that the standing reaction time in step (1) is 10 min, and the standing reaction time in step (2) is 40 min. The obtained COF material is called COF-2 material.

[0040] Example 3

[0041] A method for preparing a covalent organic framework material for removing mercury ions from water. The preparation method is basically the same as that of Example 1, except that the standing reaction time in step (1) is 20 min, and the standing reaction time in step (2) is 20 min. The obtained COF material is called COF-3 material.

[0042] Example 4

[0043] A method for preparing a covalent organic framework material for removing mercury ions from water. The preparation method is basically the same as that of Example 1, except that the standing reaction time in step (1) is 40 min, and the standing reaction time in step (2) is 60 min. The obtained COF material is called COF-4 material.

[0044] 2. Structural characterization of COFs materials

[0045] The crystal structure and morphology of the COF-1 material prepared in Example 1 were characterized by X-ray diffractometer (XRD) and scanning electron microscope (SEM), respectively. Figure 1 : This is the XRD analysis diagram of the COF-1 material in Example 1. It can be seen from the figure that a high-intensity peak is observed at 4.8° for the COF material, which is caused by the reflection of the

[100] crystal plane of the COF material. Small peaks are observed in the range of 8.4°, 12.7° and 14.6°, corresponding to the reflections of the

[110] ,

[111] and

[120] crystal planes, respectively. Due to the π-π superposition effect of COF, two small peaks can be observed at around 26.7°. The above XRD analysis results confirm that the present invention successfully prepared the COFs material.

[0046] The morphology of the COF-1 material prepared in Example 1 was observed by SEM electron microscopy. Figure 2 As shown, the morphology of the COF-1 material is similar to that of a stack of glass beads with a size of about 1 μm.

[0047] (III) Study on the adsorption performance of COFs materials prepared under different conditions for heavy metal mercury ions

[0048] The adsorption performance of a single heavy metal mercury ion was evaluated for the COFs materials (COF-1, COF-2, COF-3, COF-4) prepared in Examples 1 to 4. The specific experimental process was as follows: a certain mass of mercuric chloride was weighed and dissolved in water at pH = 2, and a mercury ion aqueous solution with a concentration of 1000 mg / L was prepared as a stock solution, and the stock solution was diluted with pure water to obtain a mercury ion aqueous solution with a concentration of 0.1 mg / L and a pH = 6 as a working solution; 3 mg of the COFs materials prepared in Examples 1 to 4 were weighed in 50 mL centrifuge tubes, 30 mL of 0.1 mg / L mercury ion aqueous solution was added thereto, and after shaking at room temperature for 12 h, the centrifuge tube was centrifuged at 10000 rpm for 5 min, the supernatant was taken and the content of mercury ions in the supernatant was determined by ICP-MS; the equilibrium adsorption rate and equilibrium adsorption amount of the COFs material for mercury ions were calculated, and the calculation formula for the equilibrium adsorption amount was as follows:

[0049] Q = ( c 0- c t ) v / m

[0050] in, Q (mg / g) refers to the adsorption capacity of the adsorbent material. c 0 (mg / mL) and c t (mg / mL) refer to the initial concentration of mercury ions and the concentration of mercury ions in the system solution at time t, respectively. v (mL) refers to the volume of the adsorption solution, m (g) refers to the mass of adsorbent material.

[0051] The specific adsorption results are shown in Table 1 and Figure 3 As shown:

[0052]

[0053] From Table 1 and Figure 3 It can be seen that the COFs materials prepared in Examples 1 to 4 all exhibited good adsorption effects on mercury ions, with adsorption rates of 81% to 91%. The above results show that the COFs materials prepared in Examples 1 to 4 at different standing reaction times can effectively remove heavy metal mercury ions in water, confirming that the preparation method proposed in the present invention can prepare COFs adsorbent materials with good adsorption effects on mercury ions in water in a relatively short time.

[0054] 4. Study on the adsorption process of mercury ions by COFs materials

[0055] The COF-1 material prepared in Example 1 is used as an experimental material to study the adsorption process of heavy metal mercury ions by the material of the present invention.

[0056] 1. Study on thermodynamic adsorption performance

[0057] (1) Experimental methods

[0058] Weigh a certain mass of mercuric chloride and dissolve it in water at pH=2 to prepare a 1000 mg / L aqueous solution of mercury ions as a stock solution. Then dilute the stock solution with pure water to prepare 0.1, 0.5, 1, 10, and 20 mg / L aqueous solutions of mercury ions (pH=6) as working solutions; accurately weigh 3 mg of COF-1 material and place it in a 50mL centrifuge tube, then add 30 mL of different concentrations of mercury ion aqueous solutions to it, and oscillate and adsorb at room temperature for 12 h; centrifuge the centrifuge tube at 10000 rpm for 5 min, take the supernatant and use ICP-MS to determine the content of mercury ions, and use the Freundlich isotherm adsorption model to fit the thermodynamic adsorption data of COFs materials to calculate the saturated adsorption capacity of COFs materials for mercury ions. The Freundlich isotherm adsorption model equation is as follows:

[0059]

[0060] in, q e (mg / g) refers to the equilibrium adsorption capacity of the adsorbent, c e (mg / mL) refers to the concentration of mercury ions in the supernatant at adsorption equilibrium. K F and 1 / n are the Freundlich isotherm adsorption constants, respectively.

[0061] (2) Results and analysis

[0062] Figure 4 They are respectively the thermodynamic adsorption curve (4a) of the COF-1 material of the present invention for heavy metal mercury ions and the fitting data diagram (4b) of the Freundlich isothermal adsorption model. Figure 4 As shown in Figure a, within the mercury ion concentration range of 0.1 to 20 mg / L, the adsorption amount of COF-1 material continues to increase with the increase of the initial mercury ion concentration. When the mercury ion concentration is low, there are relatively more active sites on the surface of COF-1 material, and the adsorption efficiency of COF-1 material for mercury ions is higher. With the increase of the initial mercury ion concentration, the number of active sites on the surface of COF-1 material that can combine with mercury ions is limited, and the adsorption amount of mercury ions slows down with the increase of concentration, but it has not reached saturation.

[0063]

[0064] The thermodynamic adsorption data were fitted using the Freundlich isotherm adsorption model. Figure 4 b and Table 2 show the correlation coefficient (R 2 ) is 0.9985, which shows that the Freundlich isotherm adsorption model is applicable to this system, and the adsorption process is mainly non-uniform multilayer adsorption. From the parameters of the Freundlich isotherm adsorption model, it can be seen that 1 / n is between 0 and 1, indicating that the adsorption process of mercury ions on COF-1 materials is relatively easy, and usually K F The larger the value, the higher the adsorption capacity. F =205.4, which indicates that COF-1 material has a large adsorption capacity for mercury ions.

[0065] 2. Kinetic adsorption performance study

[0066] (1) Experimental methods

[0067] The kinetic adsorption and removal effect of mercury ions on the COF-1 material prepared in Example 1 was studied, and the results are as follows: Figure 5 And as shown in Table 3.

[0068] The specific experimental operation is as follows: weigh a certain mass of mercuric chloride and dissolve it in water with pH=2, prepare a mercury ion aqueous solution with a concentration of 1000 mg / L as a stock solution, and then dilute it with pure water to obtain a mercury ion aqueous solution with a concentration of 0.1 mg / L (pH=6) as a working solution; accurately weigh 3 mg of COF-1 material and place it in a 50 mL centrifuge tube, then add 30 mL of 0.1 mg / L mercury ion aqueous solution, and oscillate and adsorb different reaction times (2, 5, 10, 20, 30, 60, 90, 120 min) at room temperature; centrifuge the centrifuge tube at 10000 rpm for 5 min, take the supernatant and use ICP-MS to determine the content of mercury ions, and use the pseudo-second-order kinetic model to fit the kinetic adsorption data to calculate the equilibrium adsorption amount and adsorption rate of COF-1 material for mercury ions. The pseudo-second-order kinetic model equation is as follows:

[0069]

[0070] in, q e (mg / g) and q t (mg / g) refers to the equilibrium adsorption capacity and adsorption capacity of the adsorbent, respectively. t The adsorption amount at time, k2 (g / (mg·min)) refers to the equilibrium rate constant of the pseudo-second-order kinetic adsorption model. t Refers to the adsorption time.

[0071] (2) Results and discussion

[0072] The experimental results are as follows Figure 5 As shown in Table 3, Figure 5 They are respectively the kinetic adsorption curve (5a) of heavy metal mercury ions by the COF-1 material in Example 1 of the present invention and the fitting data diagram of the pseudo-second-order kinetic model (5b).

[0073]

[0074] from Figure 5 It can be seen that within 0 to 90 min, the adsorption of mercury ions by COF-1 material gradually increases with the extension of time. As the time continues to extend, the adsorption amount tends to be flat. When the reaction time is 90 min, the adsorption of mercury ions by COF-1 material basically reaches the adsorption-desorption equilibrium. The pseudo-second-order kinetic model is used to fit and analyze the adsorption data of 5 to 30 min. The results are as follows Figure 5 As shown in Figure 3 and Table 3, the pseudo-second-order kinetic model has good linearity in fitting the adsorption data. The equilibrium adsorption amount of mercury ions on COF-1 material is 0.726 mg / g, which is close to the actual equilibrium adsorption capacity. This shows that the adsorption of mercury ions by COF-1 material is mainly a chemical adsorption process.

[0075] 3. Selective adsorption experiments

[0076] (1) Experimental methods

[0077] Select manganese ions (Mn 2+ ), cobalt ions (Co 2+ )、nickel ion(Ni 2+ ), cadmium ions (Cd 2+ ), lead ion (Pb 2+ ) and magnesium ions (Mg 2+ ) as a competitive metal ion for mercury ions, the selective adsorption and removal effect of the COF-1 material prepared in Example 1 on mercury ions in water was studied, and the results are as follows Figure 6 shown.

[0078] Specific experimental process: a certain mass of mercuric chloride, manganese chloride, cobalt chloride hexahydrate, nickel chloride, cadmium chloride, lead nitrate and magnesium chloride were weighed and dissolved in water with pH=2 to prepare a single substance stock solution with a mass concentration of 1000 mg / L, and then diluted with pure water to obtain a metal ion mixed standard working solution with a concentration of 0.1 mg / L; 3 mg of COF-1 material was accurately weighed and placed in a 50 mL centrifuge tube, and then 30 mL of 0.1 mg / L metal ion mixed standard working solution was added thereto, and oscillated and adsorbed at room temperature for 12 h; the centrifuge tube was centrifuged at 10000 rpm for 5 min, and the supernatant was taken and the content of mercury ions was determined by ICP-MS to investigate the selective adsorption and removal effect of COF-1 material on mercury ions.

[0079] (2) Results and analysis

[0080] Figure 6 This is the selective adsorption and removal effect diagram of COF-1 material for heavy metal mercury ions. Figure 6 It can be seen that the adsorption rate of COF-1 material for mercury ions in the mixed standard solution of 7 metals is 74.2%, while for the other 5 heavy metal ions such as Mn 2+ 、Co 2+ 、Ni 2+ 、Cd 2+ and Pb 2+ The adsorption rates of alkaline earth metal Mg were 2.7%, 7.5%, 0.37%, 6.3% and 31.3%, respectively. 2+ The adsorption rate is 7.9%, which indicates that the coexistence of other mixed metal ion pollutants does not have a significant effect on the adsorption of mercury ions on COF-1 materials. This reflects that COF-1 materials have good selective adsorption and removal effects on mercury ions in water and have good practical application value.

[0081] In summary, the present invention effectively overcomes the deficiencies in the prior art and has a high industrial utilization value. The above embodiments serve to illustrate the substantive content of the present invention, but do not limit the protection scope of the present invention. Those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and protection scope of the technical solution of the present invention.

Claims

1. Application of a covalent organic framework material in removing mercury ions from water, characterized in that: The preparation method of the covalent organic framework material comprises the following steps: (1) dissolving p-phenylenediamine and trialdehyde phloroglucinol in a mixed solvent, and allowing to react at room temperature to obtain a mixed solution; the molar ratio of p-phenylenediamine to trialdehyde phloroglucinol is 3:2; the mixed solvent is a mixed solvent of 1,4-dioxane and 1,3,5-trimethylbenzene; and the volume ratio of 1,4-dioxane to 1,3,5-trimethylbenzene in the mixed solvent is 4:1; (2) adding scandium trifluoromethanesulfonate to the mixed solution obtained in step (1), allowing the mixture to react at room temperature, and separating insoluble matter from the reaction solution after the reaction is completed, washing the insoluble matter, and drying the insoluble matter to obtain the covalent organic framework material for removing mercury ions in water.

2. The use according to claim 1, characterized in that , the molar ratio of p-phenylenediamine to scandium trifluoromethanesulfonate is (25-100):

1.

3. The use according to claim 1, characterized in that The standing reaction time in step (1) and step (2) is 10 to 60 min.

4. The use according to claim 1, characterized in that In step (2), the detergent for washing the insoluble matter is at least one of methanol, ethanol and acetone.

5. The use according to any one of claims 1 to 4, characterized in that In step (2), the drying temperature is 50-100°C and the drying time is 10-24 h.

Citation Information

Patent Citations

  • Functionalized covalent organic framework material as well as preparation method and application thereof

    CN115414919A

  • Covalent organic framework nanofiltration membrane and preparation method thereof

    CN116785952A